The ECG in prehospital emergency care - Brady, William, 1960-; Alibertis, Kostas (Chichester : Wiley-Blackwell, 2013)
This book exclusively addresses ECGs for prehospital emergencies, ranging from basic rhythm diagnosis to critical care applications of the electrocardiogram and advanced 12-lead ECG interpretation in the ACS patient. It provides self-testing traces covering all these conditions seen in prehospital and hospital- based environments.
Section 1: The ECG in Prehospital Patient Care. Clinical Applications of the Electrocardiogram (ECG) / Robert C Schutt, William J Brady, Steven H Mitchell -- Clinical Impact of the Electrocardiogram (ECG) / Robert C Schutt, William J Brady, Steven H Mitchell -- Interpretation of the Electrocardiogram : Single-, Multi-, and 12-Lead Analysis / Robert C Reiser, Robert C Schutt, William J Brady -- Variants of the Normal, Lead Misplacement, and Electrocardiographic Artifact Encountered in Clinical Practice / Robert C Reiser, Robert C Schutt, William J Brady -- Section 2: Cardiac Rhythms and Cardiac Dysrhythmias. Cardiac Rhythms with Normal Rates / Korin B Hudson, William J Brady -- Narrow QRS Complex Tachycardia / Courtney B Saunders, Jeffrey D Ferguson -- Wide QRS Complex Tachycardia / Michael Levy, Francis X Nolan -- Bradycardia / Korin B Hudson, J Aidan Boswick, William J Brady -- Atrioventricular Conduction Block / Steven H Mitchell, Korin B Hudson, William J Brady -- Intraventricular Conduction Block: Bundle Branch Block and Other Conduction Abnormalities / Steven H Mitchell, Richard B Utarnachitt, William J Brady -- Atrial and Ventricular Ectopic Beats / Jeffrey D Ferguson, Michael Levy, J Aidan Boswick, William J Brady -- Section 3: Acute Coronary Syndrome and the 12-Lead ECG. Ischemic Heart Disease: Anatomic and Physiologic Considerations / Peter Pollak, Peter Monteleone, Kelly Williamson, David Carlberg, William J Brady -- Historical Development of the Prehospital Electrocardiogram (ECG) / Erik Iszkula, David Carlberg, William J Brady -- Electrocardiographic Findings in Acute Coronary Syndrome / Peter Monteleone, Peter Pollak, David Carlberg, William J Brady -- Section 4: Special Populations, High-Risk Presentation Scenarios, and Advanced Electrocardiographic Techniques. The Electrocardiogram in the Pediatric Patient / Robert Rutherford, Robin Naples, William J Brady -- The Electrocardiogram in the Poisoned Patient / Steven H Mitchell, Christopher P Holstege, William J Brady -- The Electrocardiogram in Hyperkalemia / Steven H Mitchell, William J Brady -- Life-Threatening Electrocardiographic Patterns / Steven H Mitchell, Richard B Utarnachitt, William J Brady -- The Electrocardiogram in Patients with Implanted Devices / Amita Sudhir, William J Brady -- Electrocardiographic Tools in Prehospital Care / Robin Naples, Alvin Wang, William J Brady -- Wolff-Parkinson-White Syndrome / William J Brady -- Cardiac Arrest Rhythms / Amita Sudhir, William J Brady -- Section 5: Electrocardiographic Differential Diagnosis of Common ECG Presentations. Electrocardiographic Differential Diagnosis of Narrow Complex Tachycardia / Megan Starling, William J Brady -- Electrocardiographic Differential Diagnosis of Wide Complex Tachycardia / Amita Sudhir, William J Brady -- Electrocardiographic Differential Diagnosis of Bradyarrhythmia / Megan Starling, William J Brady -- Electrocardiographic Differential Diagnosis of ST Segment Elevation / Megan Starling, William J Brady -- Electrocardiographic Differential Diagnosis of ST Segment Depression / Amita Sudhir, William J Brady -- Electrocardiographic Differential Diagnosis of T Wave Abnormalities: The Prominent T Wave and T Wave Inversions / Amita Sudhir, William J Brady.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Electrocardiography; Emergency medicine -- Diagnosis; Electrocardiography; Emergency medicine -- Diagnosis; Electronic books